GENETIC DIVERSITY, HERITABILITY AND MORPHOLOGICAL CHARACTERIZATION IN BOTTLE GOURD (LAGENARIA SICERARIA (MOL.) STAND) - SHARMA, ANCHAL; S K SENGUPTA (The Bioscan, 2013)
A field experiment was conducted at Vegetable Research Farm, Maharajpur, J.N.K.V.V., Jabalpur (M.P.) during winter season in the year 2008-09 and 2009-10. The present investigation was undertaken with 16 genotypes of bottle gourd for evaluating their performance for various horticultural characters. There was a great deal of significant variation for all the characters among the genotypes. The significantly higher yield in Narendra Shivani (311.53 q/ha) might be due to higher values of yield attributes (fruit set percentage, fruit length, number of fruit per vine, fruit weight and fruit width) followed by Narendra Sanker Lauki. Whereas, the lower yield was found in case of Narendra Jyoti (101.86 q/ha), respectively due to lower yield attributes. High genotypic co-efficient of variation (GCV) was observed for fruit weight (39.48%). In all cases, phenotypic co-efficient variances were higher than the genotypic co-efficient variance. High heritability with high genetic advance in percent of mean was observed for all characters were under additive gene control and selection for genetic improvement for this trait would be effective. Among all the genotypes, Narendra Shivani, Narendra Sanker Lauki, and NS 421 gave promising results.